Analiza in določanje lastnosti parametrov nadomestnega sistema vzvojnih nihanj, ki se pojavljajo tudi na dizelskih motorjih za pogon tovornih vozil - Filipovič, Ivan (Strojniški vestnik, 2005)
This paper describes the procedure for modeling and calculating the parametersof the torsional-oscillatory system equivalent to multi-cylinder, in-line, water-cooled diesel engines in heavy-duty vehicles. As a result of a literature search and our own investigation we present models and algorithms for defining the following parameters: the moments of inertia of oscillatory masses, the stiffnesses of engine-crankshaft segments, the external and internal damping in the torsional-oscillatory system, and the excitation of gas and inertia forces. Due to the specific characteristics of the viscoelastic element, somewhat more emphasis is placed on the viscoelastic damper of torsional oscillations in internal combustion engines. For the proposed equivalent torsional-oscillatory system, a suitable model and our owncalculation program were developed. The analysis of the amplitude of twisting of individual system components in an actual engine, with and withouta torsional-oscillations damper, is given. These results are compared to the experiments conducted on an engine test-bench. The agreement between the analytical and experimental results suggests that the proposed procedure for modeling and computing the parameters of the equivalent torsional-oscillatory systems can be successfully applied in practice.
Keywords: motorji dizelski; vozila tovorna; nihanja vzvojna; modeli računski; motorna vozila; dizelski motorji; nihanje; matematični modeli